Dislocations on understanding the rule of law - Canotilho, J.J. Gomes (UNIO – EU Law Journal, 2017)
This paper analyses the problems of the rule of law in today’s legal and constitutional discourse. The criticisms the rule of law principle is subjected to, which contribute to its downgrading and to changes in the legal standards that had been progressively achieved, are especially examined, namely, the so-called hyper-protection of fundamental rights and the difficult harmonization with the idea of efficiency. Furthermore, the author identifies the de facto conditions that accentuate the identified problems, such as the systemic deficit of the European Union and the jurisdictional deficit that has become evident since the economic crisis.